Midazolam attenuates mental stress in conscious patients during cardiopulmonary resuscitation performed next bed in intensive care unit - Li, Qin (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2008)
OBJECTIVE: To evaluate the mental stress level and alterations in circulatory physiology in conscious patients during cardiopulmonary resuscitation (CPR) performed next bed in intensive care unit (ICU), and to investigate the possible effective interventions